Suberized transport barriers in plant roots: the effect of silicon. (25th April 2020) - Kreszies, Tino; Kreszies, Victoria; Ly, Falko; Thangamani, Priya Dharshini; Shellakkutti, Nandhini; Schreiber, Lukas
Abstract : Supplementation of nutrient solutions with Si did not enhance barley root suberization, suggesting that enhanced stress tolerance of plants after Si supplementation is due to other responses. Abstract: Plant roots are the major organs that take up water and dissolved nutrients. It has been widely shown that apoplastic barriers such as Casparian bands and suberin lamellae in the endo- and exodermis of roots have an important effect on regulating radial water and nutrient transport. Furthermore, it has been described that silicon can promote plant growth and survival under different conditions. However, the potential effects of silicon on the formation and structure of apoplastic barriers are controversial. A delayed as well as an enhanced suberization of root apoplastic barriers with silicon has been described in the literature. Here we review the effects of silicon on the formation of suberized apoplastic barriers in roots, and present results of the effect of silicon treatment on the formation of endodermal suberized barriers on barley seminal roots under control conditions and when exposed to osmotic stress. Chemical analysis confirmed that osmotic stress enhanced barley root suberization. While a supplementation with silicon in both, control conditions and osmotic stress, did not enhanced barley root suberization. These results suggest that enhanced stress tolerance of plants after silicon treatment is due to other responses.